Investigation into the effects of surface stripping ZnO nanosheets. (23rd February 2018) - Barnett, Chris J; Jackson, Georgina; Jones, Daniel R; Lewis, Aled R; Welsby, Kathryn; Evans, Jon E; McGettrick, James D; Watson, Trystan; Maffeis, Thierry G G; Dunstan, Peter R; Barron, Andrew R; Cobley, Richard J
Abstract: ZnO nanosheets are polycrystalline nanostructures that are used in devices including solar cells and gas sensors. However, for efficient and reproducible device operation and contact behaviour the conductivity characteristics must be controlled and surface contaminants removed. Here we use low doses of argon bombardment to remove surface contamination and make reproducible lower resistance contacts. Higher doses strip the surface of the nanosheets altering the contact type from near-ohmic to rectifying by removing the donor-type defects, which photoluminescence shows to be concentrated in the near-surface. Controlled doses of argon treatments allow nanosheets to be customised for device formation.